THE EFFECT OF PLANTING DISTANCE AND TYPES OF MANURE ON THE GROWTH AND BIOMASS OF INDIGOFERA - Darban Haryanto; Ellen Rosyelina Sasmita (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2019)
The study aims to determine the effect of planting distance and types of manure on the growth and biomass of Indigofera plants. The study was conducted in practice garden of Faculty of Agriculture UPN “Veteran” Yogyakarta, is a field experiment using a Complete Randomized Group Design consisting of J1: planting distance 1 m x 1 m ; J2: 1 m x 1,25 m ; J3: 1 m x 1,5 m ; J4: 1 m x 1,75 m. The second factor is types of manure, which consist of: M1: cow manure dosage 20 t/ha; M2: goat manure dosage 20 t/ha. The study result shows that there is no interaction between planting distance and types of manure toward growth and biomass yield of Indigofera plant. The planting distance treatment of 1 m x 1 m (J1) and planting distance of 1 m x 1,5 m (J3) gives insignificant influence on all parameters observed at 9 weeks observation after planting. The manure types treatment gives insignificant difference on all observed parameters.Keyword: planting distance, manure, indigofera